Development of Google Sites-Based E-Learning Animation Video for Learning Atomic Theory - Putri, Rizka Amalia; Rahayu, Rosika; Nurlaili, Nurlaili; Lestari, Sri; Rahmadani, Agung (Journal of Educational Sciences, 2025)
The rapid advancement of digital technology offers significant opportunities to develop innovative, interactive, and adaptive learning media that align with the learning characteristics of the 21st-century generation. This study aims to develop and evaluate animated video-based instructional materials on the topic of atomic theory development, integrated through Google Sites, and to determine their validity, practicality, and effectiveness. The research employed the Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The study involved two subject matter experts, two media experts, two instructional practitioners, and tenth-grade students from SMAIT Istiqamah YPAIT Balikpapan. The validation results indicated a high level of feasibility with a score of 94.92% (very valid). Practicality assessments yielded scores of 90.73% from teachers (very practical) and 76.74% from students (practical). The effectiveness test demonstrated improved learning outcomes, with an N-Gain score of 0.70 (medium category) and an effect size of 3.71 (very strong category). These findings suggest that Google Sites-based animated video media effectively enhance students’ conceptual understanding, motivation, and learning independence, making it a relevant and innovative alternative for digital-based chemistry learning.